(3eMGSHI GdHJQhd (B/s - (3GdbGVj, MSjfs; (3eMeO bGSe,YHO GdQRGb s ((3YeGf(B: s (3GdOGQ GdYdejI GdOhdjI ddfTQ(B, s, 2001)
(3eONd Gdi UfGYI hGSJcTGa hEfJGL GdHJQhd, GdeHGOF GdeMGSHjI GdNGUI dfTGWGJ EfJGL GdHJQhd, eMGSHI JcGdja GdESJcTGa, eMGSHI GdMUhd Ydi GdefGWb ZjQ GdeHQgfI hJMhjdgG hGdJfGRd YfgG, fabGJ GdMaQ hGdJWhjQ, eMGSHI JcGdja GdEfJGL, GMJjGWGJ GdfaW hGdZGR, eMGSHI eHjYGJ GdefGWb GdeHQgfI hZjQ GdeHQgfI, eMGSHI eHjYGJ GdfaW hGdZGR, GdEaUGM aj TQcGJ CSJcTGa hEfJGL GdHJQhds
(3eUWdMGJ hJYGQja U(B.349s
Keywords: (3GdeMGSHIs; (3GdfaWs